Recapitulating Actin Module Organization in the Drosophila Oocyte Reveals New Roles for Bristle-Actin-Modulating Proteins - Ramesh Kumar Krishnan (International Journal of Molecular Sciences, 2021)
The generation of F-actin bundles is controlled by the action of actin-binding proteins. In Drosophila bristle development, two major actin-bundling proteins—Forked and Fascin—were identified, but still the molecular mechanism by which these actin-bundling proteins and other proteins generate bristle actin bundles is unknown. In this study, we developed a technique that allows recapitulation of bristle actin module organization using the Drosophila ovary by a combination of confocal microscopy, super-resolution structured illumination microscopy, and correlative light and electron microscope analysis. Since Forked generated a distinct ectopic network of actin bundles in the oocyte, the additive effect of two other actin-associated proteins, namely, Fascin and Javelin (Jv), was studied. We found that co-expression of Fascin and Forked demonstrated that the number of actin filaments within the actin bundles dramatically increased, and in their geometric organization, they resembled bristle-like actin bundles. On the other hand, co-expression of Jv with Forked increased the length and density of the actin bundles. When all three proteins co-expressed, the actin bundles were longer and denser, and contained a high number of actin filaments in the bundle. Thus, our results demonstrate that the Drosophila oocyte could serve as a test tube for actin bundle analysis.